2002
DOI: 10.1074/jbc.m204568200
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorated Hepatic Insulin Resistance Is Associated with Normalization of Microsomal Triglyceride Transfer Protein Expression and Reduction in Very Low Density Lipoprotein Assembly and Secretion in the Fructose-fed Hamster

Abstract: To determine whether reduction of insulin resistance could ameliorate fructose-induced very low density lipoprotein (VLDL) oversecretion and to explore the mechanism of this effect, fructose-fed hamsters received placebo or rosiglitazone for 3 weeks. Rosiglitazone treatment led to normalization of the blunted insulinmediated suppression of the glucose production rate and to a ϳ2-fold increase in whole body insulin-mediated glucose disappearance rate (p < 0.001). Rosiglitazone ameliorated the defect in hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 53 publications
6
54
0
Order By: Relevance
“…Since there were no changes in the cholesterol present in VLDL, it seems reasonable that improved fasting triglyceride involves a reduction in hepatic triglyceride synthesis or its integration into apo-B100, both processes being influenced by insulin [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Since there were no changes in the cholesterol present in VLDL, it seems reasonable that improved fasting triglyceride involves a reduction in hepatic triglyceride synthesis or its integration into apo-B100, both processes being influenced by insulin [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Although the physiological basis of metabolic dyslipidaemia appears to be hepatic overproduction of apo-B-containing VLDL particles [46,47], emerging evidence suggests that intestinal overproduction of apo-B-48-containing lipoproteins in insulin-resistant states may be an important contributor to the elevation of circulating triglyceride-rich lipoproteins [17,18,48]. The present study demonstrated that intestinal cells, like hepatocytes [49,50], responded to n-3 FA and decreased the output of triglyceride-rich lipoproteins by lowering the synthesis of apo B-48 and by inhibiting the new formation of lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin acts on two key factors that regulate the initiation of VLDL assembly and the maturation of VLDL particles: microsomal triglyceride transfer protein and phosphatidylinositol 3-kinase [37][38][39][40]. Consequently, impaired insulin signalling results in increased VLDL production.…”
Section: Discussionmentioning
confidence: 99%